PENGARUH SUHU DAN LAMA FERMENTASI TERHADAP UJI ORGANOLEPTIK PADA PEMBUATAN NATA BUAH ENAU (Areng pinnata Merr) - Marselia Latumahina; Ali Awan; Dominggus Rumahlatu (BIOPENDIX, 2017)
Background: Enau is one of the natural resources in the tropics, its distribution is widespread, very necessary and easy to obtain for daily use by local people as a sustainable natural resource. Palm fruit in terms of chemical composition has a low nutritional value, but "kolang-kaling" fiber is very good for health, to reduce fruit damage, then palm fruit is processed into nata which has a high economic value. Method: Making nata de arenga pinnata Merr is aided by microorganisms, namely the bacterium Aceetobacter xylinum. The type of research used is the type of experimental research that is to see the difference in the organoleptic test scores of palm fruit (Arenga pinnata Merr). This research was conducted on December 5 to December 20, 2016. Results: The results showed that organoleptic tests had white, tasteless, chewy texture and a non-sour aroma. Conclusion: There is an influence of temperature with fermentation time on organoleptic test values ​​on the manufacture of palm fruit nata, namely the color and texture of palm fruit nata. Whereas in taste and aroma there is no influence of temperature and duration of fermentation on organoleptic test values ​​on the making of palm fruit nata.